Al-safinah al-Qadariyah - 'Abd. al-Qadir al-Jilani, d. 1166; Ibn Hajar al-'Asqalani, Ahmad ibn 'Ali, 1372-1449; Ahmad Mulla, Muhammad; Kilani, Muhammad al-Amin (Beirut : Dar al-Kutub al-'IImiyah, 2002)
35